NEW MATERIAL OF LUTRA SIMPLICIDENS (CARNIVORA, MUSTELIDAE, LUTRINAE), A KEY TAXON FOR UNDERSTANDING THE EVOLUTION OF EUROPEAN OTTERS (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2017)
Lutra lutra (Linnaeus, 1758) is the only otter living in Europe today, but the palaeodiversity of this group during the Pleistocene was much higher. Lutra simplicidens Thenius, 1965 is one of the best-known taxa from the European Quaternary fossil record, having been reported in at least eight localities in Central Europe, Britain, Italy and the Azov Sea area, with a stratigraphic occurrence spanning the mid Early to the Middle Pleistocene. However, no cranial remains of this species have been described so far. Here I analyse some unpublished material of L. simplicidens from the early Middle Pleistocene site of Voigtstedt (Germany), which consists of the right and left P4-M1 of the same individual and a complete left humerus. The comparative study of these findings highlights a number of morphological and biometrical similarities between L. simplicidens and some Mediterranean Quaternary otters, such as Lutraeximia umbra Cherin et al., 2016 from central Italy, Lutraeximia trinacriae (Burgio & Fiore, 1988) from Sicily, Sardolutra ichnusae (Malatesta, 1977) from Sardinia and Lutrogale cretensis (Symeonides & Sondaar, 1975) from Crete. These species - together with the living Lutrogale perspicillata (Geoffroy Saint-Hilaire, 1826) - form a monophyletic clade, which most probably includes also L. simplicidens, as well as several other Eurasian extinct taxa only known by fragmentary remains. These results confirm the pivotal importance of L. simplicidens for the evolution of European otters and lead to doubts about its taxonomic status, which will be solved with the discovery of new material.